Spontaneous Overgrowth of Jointing in the Working Chambers of Power Gas-Liquid Thermal Installations – Diffusion Dynamic Processes - T. V. Ryzhova; D. N. Bukharov; M. M. Arakelian; S. M. Arakelian (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The issues of the formation of inhomogeneities and cracks as well as the effects of their spontaneous healing are considered on the well-known principles and concepts of nonlinear dynamics and quantum technologies in order to fully describe the picture of possible processes of the genesis of heterogeneities and their self-organization. At the same time, the process of spontaneous overgrowth of micro-inhomogeneities in solid-state/metal products, such defects in which occur under different operating conditions, is discussed on the example of thermal power plants of various types with cyclic processes and vibrations. The mechanism of such healing is determined by dynamic processes of unsteady diffusion with certain temporal characteristics evaluated within the framework of the corresponding model concepts. A model of diffusion-limited aggregation of defects/particles implemented by the cellular automaton method from the Neumann neighborhood, a model of random and ballistic deposition, as well as a percolation approach are considered. The process of modification and development of a 3D fractured structure based on the Griffiths load theory for dislocations is described, taking into account the gradual sequential transition from a stable state to a growth stage. As a result of the action of such dynamic loads in a solidstate object, a rapid change in the parameters of microcracking is observed, which can be represented as local micro-explosions, viz. the growth and fusion of natural microcracks into larger ones; the emergence of new microcracks; the disclosure of large microcracks with the formation of defects of the next hierarchical level. In the overview aspect, the universal modes of operation of a nonlinear dynamic system, well-known in mathematics and physics and suitable for analyzing the stability and sustainability of thermal power plants, are considered. The ongoing processes are associated with different types and strategies for the development of heterogeneities, such as: collapse and stagnation; stable periodicity; parameters “at odds”; chaotic development within certain limits; disruption/sudden crisis; a sharp leap and a breakthrough in development. The proposed approaches can be useful in improving the real operational condition of chambers with working matter in power plants when they operate in various operating modes.